Výsledky výběrového šetření RESTABUS Inovativní cesty definice, měření prevalence a řešení seniorského abusu v ČR Souhrnná výzkumná zpráva - Reimerová, Klára (Masaryk University Press, 2023)
The aim of the research report is to present the results of the representative survey carried out in the RESTABUS project. This survey is the first of its kind and scope in the Czech Republic in its focus on mapping the prevalence of elder abuse, exploitation, neglect, other violence and undermining of dignity of older people (EAN). The survey was carried out among 2687 respondents aged 65 to 99 years living at home (outside residential care) and is representative of the older population in the Czech Republic. The topic of EAN is complemented by issues of the perceived prevalence of EAN in the public space, capturing attitudes towards restorative justice, and early trauma incidents (experience of violence in childhood and middle age). Thus, the research not only describes the level of prevalence of violence and ill-treatment of older people in the Czech Republic, but also maps the impact of experienced incidents on the quality of life of persons at risk, ascertains the attitudes of the older people towards the functionality of available forms of help and support, and suggests the direction of their possible further development. The report includes a methodological section, a results section and a tabular annex.